Compressive performance of steel-timber composite L-shaped columns under concentric loading. (1st May 2022) - Xu, Feiyang; Xuan, Shiqing; Li, Wei; Meng, Xinmiao; Gao, Ying
Abstract: Steel-timber composites (STCs) have emerged in the construction of large-span structures and multistory buildings. In this paper, a novel L-shaped column fabricated using STC (L-STC) was proposed. The L-STC column consisted of equal-leg angle steel and glulam. The angle steel was bonded inside the glulam. Twenty-two L-STC columns were tested under axial compression and compared with four L-shaped glulam columns as control groups. Parameters including wood species, steel ratios and column lengths were considered. The failure modes, stiffness, load-carrying capacity and ductility of the L-STC columns were analyzed. The test results demonstrated that L-STC columns displayed a (near) full composite action. The short L-STC columns failed due to crushing failure while the long L-STC columns failed due to global buckling. The stiffness and load-carrying capacity of the L-STC columns were enhanced by more than 56% and 33%, respectively. Increasing the width of the angle legs was recommended to achieve a higher load-carrying capacity. Furthermore, a finite element analysis was developed and validated. The load distribution on components of the L-STC columns was presented, and restraining effects of the timber on steel were analyzed and discussed. It was found that enhancing the timber grades, column lengths or reducing the steel ratios offered preferable lateral restraint of timber on steel. Highlights: Steel-timber composite L-shaped columns were proposed and experimentally evaluated. Enlarging the width of the encased angle legs is more effective in improving the compressive performance. Load distribution on components was investigated using the validated FE models. The confinement effects were numerically analyzed and discussed.